TRANSPORTER OF IBA1 links auxin and cytokinin to influence root architecture - Michniewicz, Marta (Dev Cell, 2019)
Developmental processes that control root system architecture are critical for soil exploration by plants, allowing for uptake of water and nutrients. Conversion of the auxin precursor indole-3-butyric acid (IBA) to active auxin (indole-3-acetic acid; IAA) modulates lateral root formation. However, mechanisms governing IBA-to-IAA conversion have yet to be elucidated. We identified TRANSPORTER OF IBA1 (TOB1) as a vacuolar IBA transporter that limits lateral root formation. Moreover, TOB1, which is transcriptionally regulated by the phytohormone cytokinin, is necessary for the ability of cytokinin to exert inhibitory effects on lateral root production. The increased production of lateral roots in tob1 mutants, TOB1 transport of IBA into the vacuole, and cytokinin-regulated TOB1 expression provide a mechanism linking cytokinin signaling and IBA contribution to the auxin pool to tune root system architecture.